Inhibitory effects of asiatic acid and CPT-11 on growth of HT-29 cells - Piyawan Bunpo (2018)
Asiatic acid is a pentacyclic triterpene contained in medicinal plants. The cytotoxic effect of this compound and its augmentative effect on the anticancer drug irinotecan hydrochloride (CPT-11) were investigated in the human colon adenocarcinoma cell line HT-29. Asiatic acid dose-dependently showed cytotoxicity in HT-29 cells. DNA fragmentation, annexin-positive apoptotic cells, and caspase-3 activation were observed in a dose-dependent manner. A caspase-3 inhibitor suppressed the DNA ladder formation in a concentration-dependent manner. Bcl-2 and Bcl-XL proteins were decreased by asiatic acid treatment. These results indicate that asiatic acid induced apoptosis in HT-29 cells via caspase-3 activation. Cytotoxic effects of combined treatment with CPT-11 and asiatic acid on HT-29 cells were further examined. Simultaneous treatment or sequential exposure first to asiatic acid and then to CPT-11 showed an additive effect. Synergism was observed when cells were first exposed to CPT-11 and then to asiatic acid. These results suggest that asiatic acid can be used as an agent for increasing sensitivity of colon cancer cells to treatment with CPT-11 or as an agent for reducing adverse effects of CPT-11.